Paint and surface coatings : theory and practice - Lambourne, R. (Ronald), 1929-; Strivens, T. A. (Ellis Horwood series in applied science and industrial technology., 1999)
Offers an account of the principles involved in the optical properties of paints, covering both the physical and aesthetic aspects of opacity and color, and discussing the physics of paint and the physical chemistry of dispersions. Reviews the polymer chemistry of common paint binders and the technology of pigment use. Also includes a section on automotive paints and automotive refinish paints addressing the demands and performance required in these markets, and chapters on the use of computers in the paint industry and health and safety explore their recent influences on coating developments.